Community Perceptions of Etawa Crossbred Goat Farming in Boyemare Village, East Lombok: Persepsi Masyarakat Desa Boyemare, Sakra Barat, Lombok Timur, terhadap Budidaya Kambing Peranakan Etawa - Saddam Ude; Muhammad Dohi; Jose Mendes; Maulana Sadid; Ryan Aryadin Putra; Amir Husaini Karim Amrullah; Hermansyah (BPFP Universitas Bengkulu, 2026)
This study aimed to determine perceptions and factors influencing the community of Boyemare Village, West Sakra Subdistrict, regarding Crossbreed Etawa (PE) goats farming. The method used in this study was a qualitative descriptive method, with data collected through structured interviews with 40 respondents. Respondents were determined using purposive sampling. The research results showed that all villagers had knowledge of cultivation PE goats. 90% farmers gained knowledge through community service activities conducted by students. The majority farmers (77,5%) expressed an interest in PE goats farming. The lack of technology for processing feed, milk, and manure is the main challenge for farmers in Boyemare (57.5%). 80% of goats farmers have experienced an economic improvement resulting in a positive impact from PE goats cultivation. We conclude that perception of the Boyemare community about PE goats is positive, as reflected in the improved economy of PE goats farmers in Boyemare Village and factors influencing farmers perceptions of PE goats farming are the relatively high price of PE goats, which has implications for farmers' income and the milk production can be consumed by family members.